PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SUCOFINDO (PERSERO) CABANG PALEMBANG - Kamariah .; Lusia Nargis (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
ABSTRACT This study aims to determine the Effect of Leadership and Work Discipline on Employee Performance at PT. Sucofindo (Persero) Palembang Branch. In this study the total population was 133 people. Sampling in this study using the Slovin formula, the number of samples taken in this study were 57 people with multiple linear regression analysis techniques. From the results of this study there is an F Test which shows that the calculated F value is 1.019 with Sig 0.000a. Searching for Table F, with dfl =2, obtained the F-table value. With F-count condition smaller than F-table (1,019 < 3,16) with Sig 0.000 a value which means smaller than alpha (0.000a > 0,05), then the conclusion that can be taken is H0 rejected which means that independent variables consist of leadership (Xl), work discipline (X2) together have a significant effect on the dependent variable (Y) in the form of employee performance. There is at test showing that the leadership variable has a Sig.0,000 > 0.05 means significant. Where as t count 5.551 > fromt-table (n - k, 57 – 2 = 55) 0.2609 means that H0 is rejected. So that leadership partially has a significant effect on employee performance. There is attest showing that the work discipline variable has a Sig value of 0.000 > 0.05 meaning significant. Where as t count 6,514 > from t-table (n k, 57 – 2 = 55) 0,2609 means that H0 is rejected. So that the work discipline partially has a significant effect on employee performance. Implementation is an effort to improve performance can be done by improving leadership and work discipline which in turn can improve performance. Keywords: Performance, Leadership and Work Discipline